Followership Affecting to Work Performance of Personnel in Basic Education Institutions Chom Phra District under Surin Primary Educational Service Area Office 1 - Saengsai, Udomsak; Wisetsri, Suparp; Nimprang, Pinij; Promtuang, Petchara; Siwina, Kittisak (Journal for Developing the Social and Community, 2026)
Background and Aims: Followership is a process by which personnel demonstrate competence, responsibility, and cooperation in working with leaders and colleagues. It plays a crucial role in supporting decision-making. Quality followers do not merely follow orders but also take initiative, are assertive, responsible, enthusiastic, and collaborate constructively with leaders, thus contributing to effective operations. This research aims to 1) study the followership behavior of personnel in basic education institutions; 2) study the performance effectiveness of personnel in basic education institutions; 3) study the relationship between followership and performance effectiveness in basic education institutions; and 4) study the impact of followership on performance effectiveness in basic education institutions. Methodology: This was a survey research. The sample consisted of 196 teachers in primary schools. The sample size was determined using the Krejcie-Morgan table, employing stratified random sampling based on school size. The data collection instrument was a 5-level Likert scale questionnaire with a reliability coefficient of 0.905. Statistical analyses included mean, standard deviation, Pearson correlation coefficient, and stepwise multiple regression analysis. Results: The findings revealed that: 1) The overall level of followership in basic education institutions was high. 2) The overall performance efficiency of personnel in basic education institutions was high. 3) There was a moderate positive correlation (rXY = 0.57) between followership and performance efficiency in basic education institutions, statistically significant at the .05 level. 4) Three aspects of followership that influenced performance efficiency in basic education institutions, namely effective followership, adaptive followership, and survival followership, collectively explained 47.70% of the variance affecting performance efficiency, statistically significant at the .05 level. Conclusion: Overall, teachers in primary education institutions exhibit a high level of followership and high work performance. Followership has a moderate positive correlation with work performance. The aspects of followership that influence work performance include effective followership, adaptive followership, and survival followership, which collectively explain 47.70% of the variance affecting work performance.